2020
DOI: 10.1177/1538192720918369
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Latinas in STEM at an R1 Higher Education Institution in Texas

Abstract: This study examined the success and persistence of Latina students in the complex environment of science, technology, engineering, and mathematics (STEM) fields at a Tier 1 Research higher education institution in Texas. For this qualitative study, 10 Latina students pursuing STEM majors were interviewed within a framework focusing on Greene’s resilience theory. Results of this study suggest a strong likelihood for Latinas to succeed in STEM fields because of their development of resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Latinx students describe how their persistence in STEM majors is derived from wanting to model success for younger siblings and to financially support their families (Aguirre et al, 2020; Gonzalez et al, 2020). Through participation in ethnic-based engineering organizations, students activate community cultural wealth (CCW) to establish family-like relationships with peers and resist racial stereotypes (Revelo, 2015; Revelo & Baber, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Latinx students describe how their persistence in STEM majors is derived from wanting to model success for younger siblings and to financially support their families (Aguirre et al, 2020; Gonzalez et al, 2020). Through participation in ethnic-based engineering organizations, students activate community cultural wealth (CCW) to establish family-like relationships with peers and resist racial stereotypes (Revelo, 2015; Revelo & Baber, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on Latinas, Hispanic women, Chicanas, and Mestizas (and other ethno‐political designations of these groups of raced women) in STEM attend to the intersectionally‐linked raced‐gendered‐ethnic‐linguistic oppression these women face (Cantú, 2012; Gonzalez et al, 2020; Stevenson et al, 2019). Such experiences impact how these women recognize their own power to succeed in STEM juxtaposed to the external validation they seek in confirming their ability to succeed in STEM from those “normalized” as representing a STEM identity (Rodriguez et al, 2019).…”
Section: Why Women Of Color In Stem?mentioning
confidence: 99%
“…Another study investigated mechanisms of resilience among Latinx undergraduates and found intrinsic value orientation to be one key determinant in fostering resilience (Cavazos et al, 2010). Moreover, researchers have suggested intrinsic motivation to be a precursor to resilience, indicating a sequential pattern (Gonzalez et al, 2022). In sum, it is reasonable to expect that greater intrinsic value orientation may equip Latinx undergraduates with a stronger capacity to develop resilience, subsequently combat unjust psychosocial adversity (e.g., discrimination), and reduce the risk of adverse mental health outcomes.…”
Section: Intrinsic Value Orientation Among Hispanic/latinx Undergradu...mentioning
confidence: 99%